OPTIMALISASI ASIA FOREST PARTNERSHIP (AFP) TERHADAP ILLEGAL LOGGING DI RIAU - Putri Laura Wanda; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The problem of illegal logging causes various disasters such as flood and landslide,this thing is involved with the deforestasi and degradation of environment that keep onhappening.In general, this research is meant to analyze the factors that hampers the programmof Asia Forest Partnership (AFP) and the efforts that are implemented in doing theprogramms to solve illegal logging.The method of data collecting is done by collecting secunder data, then analyzed inqualitative to obtain the draft about the main problem by using deductive method. Themethod of this research is the method of qualitative descriptive. The data is obtained throughsecunder data such as, book, journal, magazine, newspaper and website.From the result of research, that the programms that are implemented Asia ForestPartnership (AFP) to solve the practice of illegal logging as one of the effort of solvingtowards the criminal act based on the determination of cooperation between IndonesiaGovernment especially the government of Riau Province and Japan with the memberscountries of AFP, which one as the impact of illegal logging can cause many disadvantagesboth in the government, society, forest, environment and its ecosystem, also experience theobstacle in implementation process of the programm. So various efforts are implemented tosolve the practice of illegal logging.The effort that is implemented by AFP to solve thepractice of illegal logging, namely the preventive effort, and represive effort.Keywords: Asia Forest Partnership, Illegal Logging, Riau’s forest.